2016
DOI: 10.1007/s10984-016-9222-9
|View full text |Cite
|
Sign up to set email alerts
|

Museums as avenues of learning for children: a decade of research

Abstract: In this review, we focus on the museum activities and strategies that encourage and support children's learning. In order to provide insight into what is known about children's learning in museums, we examined study content, methodology and the resultant knowledge from the last decade of research. Because interactivity is increasingly seen as essential in children's learning experiences in a museum context, we developed a framework that distinguishes between three main interactivity types for facilitating stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 55 publications
1
84
0
13
Order By: Relevance
“…Our two main results support the results of two recent meta-studies (Andre et al 2017;Rennie 2014) but also provide new information in relation to contemporary studies (Vennix et al 2017) related to museums and science centres as informal open learning environments.…”
Section: Resultssupporting
confidence: 90%
“…Our two main results support the results of two recent meta-studies (Andre et al 2017;Rennie 2014) but also provide new information in relation to contemporary studies (Vennix et al 2017) related to museums and science centres as informal open learning environments.…”
Section: Resultssupporting
confidence: 90%
“…Nowadays, museums have the task of not only storing and preserving historical values, but also of using them for learning purposes [13]. From the perspective of educational sciences, learning in museums is one form of situated learning [14,15] where access to a variety of knowledge is possible, providing learning opportunities that enhance individuals' interest in knowledge accumulated in museums, interacting with virtual artefacts, and enabling them to interact with substance and concreteness with the museum's intangible artefacts [16].…”
Section: Learning In Museumsmentioning
confidence: 99%
“…The age group for which the material can be used Adults (18+) School-age children (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Minors (up to 7)…”
Section: Focus Of Attentionmentioning
confidence: 99%
“…'s work is a review of research which found 44 studies on children's learning in museums from 2000–2012—but only six of these studies took place in children's museums, and only four of those six were empirical studies offering research‐based findings (Andre et al. ). This suggests that we really have very little evidence that children's museums are effective at reaching goals such as cultivating curiosity and fostering broad‐mindedness.…”
Section: Research In Children's Museumsmentioning
confidence: 99%